Thermal analysis through cylindrical porous fin having insulated tip: a hybrid nanomaterial approach. (22nd June 2021) - Ramesh, G K; Manohar, G R; Venkatesh, P; Gireesha, B J; Shah, Nehad Ali; Chung, Jae Dong
Abstract: Two kinds of hybrid nanomaterial flow through cylindrical fin are examined under the presence of conduction, convection and radiation. Darcy law model is used to develop the heat equation. With the help of Maple, the non-dimensional thermal equation is numerically solved using the fourth and fifth order of Runge–Kutta Fehlberg. The impact of convection parameter, wet porous parameter, radiation parameter, power law index, ambient temperature and solid volume fraction are discussed through the graphs. It is found that higher values radiation parameter reduces the temperature whereas solid volume fraction enhances the temperature.